2D Materials: Emerging Applications of Elemental 2D Materials (Adv. Mater. 7/2020). Issue 7 (18th February 2020) - Glavin, Nicholas R.; Rao, Rahul; Varshney, Vikas; Bianco, Elisabeth; Apte, Amey; Roy, Ajit; Ringe, Emilie; Ajayan, Pulickel M.
Abstract : In article number 1904302, Nicholas R. Glavin, Pulickel M. Ajayan, and co‐workers review recent progress in applications for an exciting class of nanomaterials referred to as elemental 2D materials. The cover image depicts the main group elements of interest and lattice structures that drive unique properties for applications including electronics, optoelectronics, and energy. Image by Dr. Jo Richers (www.jorichers.com ).